Camp pain : talking with chronic pain patients - Jackson, Jean E. (Jean Elizabeth), 1943- (University of Pennsylvania Press, 2000)
Based on fieldwork in a pain treatment center, "Camp Pain" focuses on patients' perspectives-on their experiences of pain and what these experiences mean to them